2021
DOI: 10.1002/jwmg.22009
|View full text |Cite
|
Sign up to set email alerts
|

Wild Turkey Nest Success in Pine‐Dominated Forests of the Southeastern United States

Abstract: Nest success is a primary component of productivity for wild turkeys (Meleagris gallopavo; turkeys) and there is concern that turkey productivity is declining across the southeastern United States. We evaluated the influence of nest site and landscape characteristics on risk of nest failure for turkeys in pine (Pinus spp.)‐dominated forests across the southeastern United States. We used Cox proportional hazard models to evaluate daily hazard of nest failure associated with nest site and landscape metrics withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…Researchers have noted similar observations previously, and attributed synchronous nesting behaviors at the population level to the potential that photoperiod most influences timing of reproduction (Healy 1992, Migaud et al 2006, Walton et al 2011. We also noted that average dates of first nest initiation for female wild turkeys on our site were comparable to dates reported across populations throughout the southeastern United States (Thogmartin and Johnson 1999, Palmer et al 2013, Crawford et al 2021. Conversely, within social groups we found substantive temporal variation in timing of nest initiation within years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Researchers have noted similar observations previously, and attributed synchronous nesting behaviors at the population level to the potential that photoperiod most influences timing of reproduction (Healy 1992, Migaud et al 2006, Walton et al 2011. We also noted that average dates of first nest initiation for female wild turkeys on our site were comparable to dates reported across populations throughout the southeastern United States (Thogmartin and Johnson 1999, Palmer et al 2013, Crawford et al 2021. Conversely, within social groups we found substantive temporal variation in timing of nest initiation within years.…”
Section: Discussionsupporting
confidence: 88%
“…We also observed that ˜30% of successful initial first nests were produced by ˜4% of females in our population, females we presumed to be dominant within their respective social groups. We note that these initial first nests by default were successful early in the nesting season, and previous works have noted the importance of successful early nesting attempts in sustaining wild turkey populations (Porter et al 1983, Crawford et al 2021. Contemporary literature has detailed the ecological significance of having females be successful at hatching clutches early in the nesting season for various species, including willow ptarmigan (Lagopus lagopus ; Wilson et al 2007) and greater sandhill cranes (Antigone canadensis ; Ivey and Dugger 2008).…”
Section: Discussionmentioning
confidence: 67%
“… 1 Bakner et al (2019), 2 Badyaev and Faust (1996), 3 Badyaev et al (1996), 4 Byrne and Chamberlain (2018), 5 Chamberlain et al (2012), 6 Chamberlain et al (2020), 7 Conner et al (2006), 8 Crawford et al (2021), 9 Diefenbach et al (2012), 10 Eriksen et al (2010), 11 Fuller et al (2013), 12 Hubbard et al (1999a), 13 Kane et al (2007), 14 Kilburg et al (2014), 15 Lavoie et al (2017), 16 Little et al (2014), 17 Little et al (2016), 18 Lohr et al (2020), 19 Lowrey et al (2000), 20 Miller, Leopold, and Hurst (1998), 21 Miller, Burger, et al (1998), 22 Metzler and Speake (1985), 23 Moore et al (1993), 24 Niedzielski and Bowman (2015), 25 Norman et al (2001), 26 Norman et al (2004), 27 Pack et al (1999), 28 Paisley et al (1998), 29 Petty et al (2005), 30 Pittman and Krementz (2016), 31 Porter et al (1983), 32 Pollentier et al (2014), 33 Reynolds and Swanson (2010), 34 Roberts and Porter (1998a), 35 Roberts and Porter (1998b), 36 Seiss et al (1990), 37 Thogmartin and Johnson (1999), 38 Tyl et al (2020), 39 Vangilder and Kurzejeski (1995), 40 Wright et al (1996), 41 Wood et al (2019), 42 Yeldell et al (2017). …”
Section: Resultsmentioning
confidence: 99%
“…Replicated studies examining phenology‐specific movement ecology on wild turkeys are rare (Hall et al 2006, 2007), as are studies that allow for population‐level comparisons across a broad spatial extent (Cohen et al 2018, Bakner et al 2019, Crawford et al 2021). Population‐level scaling can significantly increase the strength and accuracy of biological inferences about space use and, by definition, resource use (Börger et al 2006, van Beest et al 2011).…”
mentioning
confidence: 99%